A privacy-preserving reputation system with user rewards. (15th February 2017) - Busom, N.; Petrlic, R.; Sebé, F.; Sorge, C.; Valls, M.
Abstract: Reputation systems are useful to assess the trustworthiness of potential transaction partners, but also a potential threat to privacy since rating profiles reveal users' preferences. Anonymous reputation systems resolve this issue, but make it difficult to assess the trustworthiness of a rating. We introduce a privacy-preserving reputation system that enables anonymous ratings while making sure that only authorized users can issue ratings. In addition, ratings can be endorsed by other users. A user who has received a pre-defined number of endorsements can prove this fact, and be rewarded e.g. by receiving a "Premium member" status. The system is based on advanced cryptographic primitives such as Chaum-Pedersen blind signatures, verifiable secret sharing and oblivious transfer.